Successful and Less Successful Students' Perceptions of A Good Speaking Lecturer - Idrisu Farisu Robbi Hababa (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This study done to know the successful and less successful students perceive a good model of speaking lecturer in English department of Universitas Islam Malang, and the similarities between successful and less successful student’s perception of a good speaking lecturers. This study classified to descriptive quantitative research. The finding of the study showed classroom atmosphere as Speaking lecturer who is relaxed but obvious get very strong belief in SS with score 80% and 73% in LS it become the highest score of all categories. In the lowest score successful and less successful students have the same believe that they do not please to the lecturer who often come late. with each score; SS=38%, LS=39%. It becomes the lowest level in all items. In conclusion, the problems most discussed are about the qualified interaction between lecturers and students, as well as clarity about the strategy for delivering material and the comfort atmosphere in the classroom that agreed between the two parties. Then also the personal discipline of the lecturer as the educator towards the process of improving speaking skills.Key words: Good speaking lecturer, Successful students, Less successful students.